JVG9, a benzimidazole derivative, alters the surface and cytoskeleton of Trypanosoma cruzi bloodstream trypomastigotes - Dylan L Díaz-Chiguer; Francisco Hernández-Luis; Benjamín Nogueda-Torres; Rafael Castillo; Olivia Reynoso-Ducoing; Alicia Hernández-Campos; Javier R Ambrosio (Memorias do Instituto Oswaldo Cruz, 2014)
Trypanosoma cruzi has a particular cytoskeleton that consists of a subpellicular network of microtubules and actin microfilaments. Therefore, it is an excellent target for the development of new anti-parasitic drugs. Benzimidazole 2-carbamates, a class of well-known broad-spectrum anthelmintics, have been shown to inhibit the in vitro growth of many protozoa. Therefore, to find efficient anti-trypanosomal (trypanocidal) drugs, our group has designed and synthesised several benzimidazole derivatives. One, named JVG9 (5-chloro-1H-benzimidazole-2-thiol), has been found to be effective against T. cruzi bloodstream trypomastigotes under both in vitro and in vivo conditions. Here, we present the in vitro effects observed by laser scanning confocal and scanning electron microscopy on T. cruzi trypomastigotes. Changes in the surface and the distribution of the cytoskeletal proteins are consistent with the hypothesis that the trypanocidal activity of JVG9 involves the cytoskeleton as a target.